Factors Affecting Accounting Student's Interest In Following Professional Certification - Anas Meliana, Ervina; Febri Nugroho, Naufal; Dwi Astuti, Christina (Devotion : Journal of Research and Community Service, 2022)
This study aims to obtain empirical evidence of the factors that influence the interest of accounting students to take a professional certification. The independent variables in this study are capability, attitudes, subjective norms, perceived behavioral control, career opportunities, and constraints. The dependent variable used is the interest of accounting students to take a professional certification. This study uses primary data collected through a google form. The population of this research is active accounting undergraduate students with universities located in Jakarta, Bogor, Depok, Tangerang, and Bekasi (JABODETABEK). The sampling technique of this research is nonprobability sampling with purposive sampling method, with the number of samples used as many as 155 samples. This research uses multiple linear regression analysis methods. The results of this study showed the variables of capability, behavior control, and career opportunities affect the interest of accounting students to take a professional certification. While the variables of attitude, subjective norms, and constraints do not affect the interest of accounting students to take professional certification